CCp5A Protein from Toxoplasma gondii as a Serological Marker of Oocyst-driven Infections in Humans and Domestic Animals - Santana, Silas S.; Gebrim, Luiz C.; Carvalho, Fernando R.; Barros, Heber S.; Barros, Patrício C.; Pajuaba, Ana C. A. M.; Messina, Valeria; Possenti, Alessia; Cherchi, Simona; Reiche, Edna M. V.; Navarro, Italmar T.; Garcia, João L.; et al. (Frontiers in Microbiology, 2015)
Considering that the current immunoassays are not able to distinguish the infective forms that cause Toxoplasma gondii infection, the present study was carried out to evaluate the reactivity of two recombinant proteins (CCp5A and OWP1) from oocyst/sporozoite, in order to differentiate infections occurring by ingestion of oocysts or tissue cysts. The reactivity of the recombinant proteins was assessed against panels of serum samples from animals (chickens, pigs, and mice) that were naturally or experimentally infected by different infective stages of the parasite. Also, we tested sera from humans who have been infected by oocysts during a well-characterized toxoplasmosis outbreak, as well as sera from pregnant women tested IgM+/IgG+ for T. gondii, which source of infection was unknown. Only the sporozoite-specific CCp5A protein was able to differentiate the parasite stage that infected chickens, pigs and mice, with specific reactivity for oocyst-infected animals. Furthermore, the CCp5A showed preferential reactivity for recent infection by oocyst/sporozoite in pigs and mice. In humans, CCp5A showed higher reactivity with serum samples from the outbreak, compared with serum from pregnant women. Altogether, these findings demonstrate the usefulness of the CCp5A protein as a new tool to identify the parasite stage of T. gondii infection, allowing its application for diagnosis and epidemiological investigations in animals and humans. The identification of parasite infective stage can help to design effective strategies to minimize severe complications in immunocompromised people and, particularly, in pregnant women to prevent congenital infection.